Safety and efficacy of Rotigotine in hospedalized patients with Vascular Parkinsonism aged 75 and older: effects on movement, praxis capacities, time-space orientation, quality of life and adherence to medical therapy. - Marchitto, Nicolino; Sindona, Francesco; Pannozzi, Alberto; Dalmaso, Serenella Gioia; Anticoli, Sabrina; Raimondi, Gianfranco (Acta Biomedica Atenei Parmensis, 2019)
In hospitals without stroke unit Department, the patients with acute ischemic stroke are stabilized in First Aid and sent to the Department of Internal Medicine. During the hospedalization period the patients undergo medical therapy for the stabilization of hemodynamic parameters and instrumental examinations for the determination of cardiovascular risk and thromboembolic evaluation. All patients are subjected to multidimensional evaluation of cognitive, praxis capacities, spatial-temporal orientation, quality of life and adherence to medical therapy. The aim of this study is evaluate the effect of Rotigotine patch on the impairment of neuro-cognitive capacity throught a continuous dopaminergic stimulation with transdermal administration. We have observed 19 patients (10 male and 9 female with range age 75-92 yrs) with Acute Ischemic Stroke stabilized in First Aid Depatment. The outcomes were the neurological changes from the baseline to 7 days in the clinical summury score on MMSE (on a scale from 0 to 30, with higher scores indicating fewer symtoms and lower physical limitations), Morinsky scale (on scale from 0 to 8, indicating adherence to therapy) and swallowing test (acts/minute). During the first week the patients were undergone to treatment with rotigotine 2 mg/24 hours. At the end of the treatment we obtained a statistically significant correlation about improvement of MMSE, Morinsky scale and swallowing test from a basal value. Rotigotine transdermal patches could be a new useful approach in the treatment of elderly hospetalized patients with acute ischaemic stroke correlated with cognitive impairment. Data shown that low dose of rotigotine patch could improves cognitive and praxis functions and therefore the quality of life of the hospitalized elderly patients. Rotigotine was effective and well-tolerated when used in routine clinical practice. Our data gave comfortable results but further evaluation are needed to have conclusive results.